Reconnaissance of philanthropy - Christou, Prokopis A.; Hadjielias, Elias; Farmaki, Anna (My University, 2019)
The amount of academic attention given to the notion of philanthropy has increased recently. Despite its significance at an organizational and societal level, philanthropy remains a rather obscure notion – an issue that the present study aims to address. In-depth interviews were conducted with owners of organizations within a rural tourism context who were reciprocally appreciated for their anthropocentricity. The findings reveal that philanthropy should not be restricted to financial aid or charity organizations; it should be expressed with intangible offerings and channeled towards customers and employees alike. The research outcomes make it possible to construct a theoretical conceptual diagram to guide both future researchers and managers of organizations who aspire to acquire a more anthropocentric stance.
Keywords: Corporate social responsibility; Philanthropy; Rural tourism